Correction to “Choline chloride enables low-severity NaOH/Triton-X 100 pretreatment and lignin upgrading to enriched aromatic bio-oil and porous biochar” [Chem. Eng. J. 2026;538:176853. https://doi.org/10.1016/j.cej.2026.176853] - S. Al Azad; E. Kargaran; M. Saleknezhad; Y. Cheng; C. Quan; J. Chen; C. Sun; M. Madadi; F. Sun (Chemical Engineering Journal, 2026)

An evaluation of fish and invertebrate mercury concentrations in the Caribbean Region - Linroy D. Christian; Mark E. H. Burton; Azad Mohammed; Wendy Nelson; Tahlia Ali Shah; Laël Bertide-Josiah; Helen G. Yurek; David C. Evers (Ecotoxicology, 2024)
Mercury is a ubiquitous pollutant of global concern but the threat of exposure is not homogenously distributed at local, regional, or global scales. The primary route of human exposure to mercury is through consumption of aquatic foods, which are culturally and economically important in the wider Caribbean Region, especially for Small Island Developing States (SIDS). We compiled more than 1600 samples of 108 unique species of fish and aquatic invertebrates collected between 2005 and 2023 from eleven countries or territories in the wider Caribbean Region. There was wide variability in total mercury concentrations with 55% of samples below the 0.23 µg/g wet weight (ww) guideline from the U.S. FDA/EPA (2022) for 2 or 3 weekly servings and 26% exceeding the 0.46 µg/g ww guideline consistent with adverse effects on human health from continual consumption, particularly for sensitive populations. Significant relationships were found between total mercury concentrations and taxonomic family, sampling country, fish length, and trophic level. The data analyzed here support the need for further sampling with concrete geospatial data to better understand patterns and mechanisms in mercury concentrations and allow for more informed decision making on the consumption of fish and invertebrates from the wider Caribbean Region as well as supporting efforts to evaluate the effectiveness of national, regional, and international mercury policies.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Altered regulation of the T-cell system in patients with CRPS - Jens Heyn; Shahnaz C. Azad; Benjamin Luchting (Inflammation Research, 2019)

Correction to: Polymyxin B causes DNA damage in HK-2 cells and mice - B. Yun; T. Zhang; M. A. K. Azad; J. Wang; C. J. Nowell; P. Kalitsis; T. Velkov; D. F. Hudson; J. Li (Archives of Toxicology, 2018)

Polymyxin B causes DNA damage in HK-2 cells and mice - B. Yun; T. Zhang; M. A. K. Azad; J. Wang; C. J. Nowell; P. Kalitsis; T. Velkov; D. F. Hudson; J. Li (Archives of Toxicology, 2018)

Emerging evidence for CHFR as a cancer biomarker: from tumor biology to precision medicine - Sarah Derks; Arjen H. G. Cleven; Veerle Melotte; Kim M. Smits; Johann C. Brandes; Nilofer Azad; Wim van Criekinge; Adriaan P. de Bruïne; James G. Herman; Manon van Engeland (Cancer and Metastasis Reviews, 2013)

Adaptation of Drosophila melanogaster to increased NaCl concentration due to dominant beneficial mutations - Mingcai Zhang; Priti Azad; R. C. Woodruff (Genetica, 2011)

Distribution of arbuscular mycorrhizal fungi in marshy and shoreline vegetation of Deepar Beel Ramsar Site of Assam, India - Bula Choudhury; M. C. Kalita; P. Azad (World Journal of Microbiology and Biotechnology, 2010)

Variability in Symbiotic Effectiveness of Native Rhizobia in Acid Stress - B. Choudhury; P. Azad; M. C. Kalita (Current Microbiology, 2010)

Rapid increase in viability due to new beneficial mutations in Drosophila melanogaster - Priti Azad; Mingchai Zhang; R. C. Woodruff (Genetica, 2010)

Coastal Aquaculture Development in Bangladesh: Unsustainable and Sustainable Experiences - A. Kalam Azad; Kathe R. Jensen; C. Kwei Lin (Environmental Management, 2009)

A C-terminal domain of HIV-1 accessory protein Vpr is involved in penetration, mitochondrial dysfunction and apoptosis of human CD4+ lymphocytes - C. Arunagiri; I. Macreadie; D. Hewish; A. Azad (Apoptosis, 1997)

Expression and analysis of the NS2 protein of influenza A virus - A. C. Ward; L. A. Castelli; A. C. Lucantoni; J. F. White; A. A. Azad; I. G. Macreadie (Archives of Virology, 1995)

Expression and characterisation of the influenza A virus non-structural protein NS1 in yeast - A. C. Ward; A. A. Azad; I. G. Macreadie (Archives of Virology, 1994)

Relationships between rhizoplane and rhizosphere bacteria and verticillium wilt resistance in potato - H. R. Azad; J. R. Davis; W. C. Schnathorst; C. I. Kado (Archives of Microbiology, 1985)